The Atlas of Religious or Belief Minority Rights in the EU: First remarks on Belief Organisations (Stato, Chiese e pluralismo confessionale, 2024)
ABSTRACT: This paper focuses on the first results of the Atlas of Religious or Belief Minority Rights in the EU regarding the legal status of Belief Organisations. The first part of this work describes “Belief Organisations”, focusing on why they are included in the Atlas, and analyses the growth of atheism and agnosticism in the countries covered by the project. The second part focuses on some of the findings that emerge from Atlas data, providing a few (provisional) remarks.SUMMARY: 1. The Atlas of Religious or Belief Minority Rights in the EU: a brief introduction - 2. Belief Organisations as actors in the religious field - 3. The religious demography of atheism and agnosticism - 4. About Belief Organisations - 5. Focus on Belief Organisations: first findings.